A implementação do juiz das garantias como retoque democrático em face do procedimento do tribunal do júri - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The present work seeks to analyze the recent provisions implemented concerning the institution of the Judge of Guarantees in Brazilian Criminal Procedure, based on Law No. 13,964/2019 (known as the "Anti-Crime Package") and the interpretations provided by the Federal Supreme Court in the judgment of Direct Actions of Unconstitutionality (ADIs) No. 6,298, 6,299, 6,300, and 6,305, highlighting the main attributions and competencies assigned to the new jurisdictional figure. Initially, there is a brief explanation of the process flow for cases under the jurisdiction of the Jury procedure and the STF's understanding during the judgment of the aforementioned ADIs, particularly regarding the exclusion of the new institute within the Jury Court procedure and the contribution that the Judge of Guarantees brings to the current criminal process, aiming to facilitate the realization of the accusatory system and the assurance of the desired democratic criminal process. Subsequently, the fundamental principles underpinning the specific Jury procedure are analyzed, along with a discussion on the STF's stance regarding the exclusion of the new jurisdictional figure in this procedure and the guarantee of the principle of impartiality provided for in infraconstitutional legislation. The contribution of the Judge of Guarantees to the Jury procedure is highlighted, especially in the first phase of the process, known as "judicium accusationis," where the single judge is responsible for rendering one of four possible decisions: indictment, dismissal, reclassification, or summary acquittal. Considerations are made regarding the necessity of distancing the single judge during the investigative phase to prevent cognitive contamination, which could compromise the judge's fundamental impartiality in the criminal process. Finally, the Theory of Cognitive Dissonance and its effects on the magistrate responsible for conducting criminal jurisdiction are considered, along with the implementation of the Judge of Guarantees as a reinforcement of impartiality and protection of individual rights and guarantees.
Keywords: Processo Penal; Juiz das garantias; Imparcialidade (Direito); Tribunais penais; Criminal procedure; Judge of guarantees; CNPQ::CIENCIAS SOCIAIS APLICADAS